The impact of the Fourth Industrial Revolution on the survival of employee skills sets in the retail environment - Ramlall, Sariksha (The IIE, 2020)
The Fourth Industrial Revolution has taken the world by storm through advanced technology. The various technologies of the Fourth Industrial Revolution are blurring the lines between the physical, digital and biological spheres of global production systems (Martin, 2017). The current pace of technological development is exerting profound changes on the way people live and work in which, employee skills sets have to constantly be improved to keep up and remain relevant in line with the technologies of The Fourth Industrial Revolution (Martin, 2017). Employees have had to improve their skills sets to survive this industrial revolution as well as familiarise themselves with the new modern forms of technology. In the retail environment online shopping has increased due to mobile applications and artificial intelligence, whilst this innovation keeps growing many jobs are being lost at the same time. This study was conducted using an interpretivist, qualitative approach to gain a rich in-depth understanding of how employees in the retail environment are going about to ensure the relevance of their skills sets within the context of the Fourth Industrial Revolution. Semi – structured interviews formed the data collection method, which enabled the researcher to gain a greater understanding on the research participants views. Thereafter the transcripts were analysed to develop themes around the first - order data. The theoretical framework of this study is based on the skills development theory, Katz’ three skill approach and Mumford’s skills model of leadership. This study concludes that due to the rapid growth and advancements of artificial intelligence as well as various other technologies, businesses have had to consistently evolve and keep up with these advancements. There has been a huge gap in employee skillset and the technology of today. Employees have had to attend various forms of training regarding such technologies. On the other hand, many employees in the retail environment have lost their jobs either because their jobs were replaced by artificial intelligence or because they did not meet the necessary skills sets requirements to remain relevant enough in their jobs.
Keywords: Fourth Industrial Revolution (4IR); Retail; Employee skills; Artificial intelligence (AI)